Precompetitive anxiety and self-confidence during the 2023 Finnish Padel championship in high level men’s players - Conde-Ripoll, Rafael; Escudero-Tena, Adrián; Suárez-Clemente, Vicente Javier; Bustamante-Sánchez, Álvaro (Frontiers in Psychology, 2023)
The aim of the current study was to assess precompetitive anxiety and self-confidence in high level men´s padel players from Finland. 28 men´s padel players from the highest category participated in the research (87.5% of the target population). The CSAI-2R (Competitive State Anxiety Inventory-2 Revised) and STAI-S (State-Trait Anxiety Inventory -State) questionnaires were used and descriptive and inferential analyzes were performed, including the Kruskal Wallis´s H and Mann-Whitney´s U tests. The results show that seeded players presented lower levels of cognitive anxiety (η 2 = 0.111). Moreover, losers of first round presented more state anxiety than winners (η 2 = 0.302). Before the first match, state anxiety was higher than prior to the second match (η 2 = 0.148). Furthermore, lower ranked players of first round, compared to second, presented more state anxiety and somatic anxiety (η 2 = 0.487 and η 2 = 0.277, respectively). However, according to the results obtained, self-confidence was not affected by any of the variables analyzed (ranking, seed, result or round). These findings may be of great interest to players, coaches and sports psychologists, as they allow an enhanced comprehension of the player's level of anxiety and self-confidence.